2014
DOI: 10.1074/jbc.m114.578872
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of F1-ATPase Rotational Catalysis by the Carboxyl-terminal Domain of the ϵ Subunit

Abstract: Background:The ⑀ subunit inhibits F 1 -ATPase activity. Results: Truncation of helix 2 or a point mutation in loop 2 of the ⑀ subunit decreased its inhibitory effects on subunit rotation. Conclusion: Helix 2 and loop 2 play pivotal roles in inhibitory regulation of F 1 rotational catalysis. Significance: Structure-based studies on the ⑀ subunit function are critical for understanding the mechanism underlying rotational catalysis of ATP synthase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…The very C‐terminal helix 2 in the ε e state interacts with the subunits α, β and γ . For some bacterial enzymes it was shown that the CTD of subunit ε has an ATP‐binding motive that can act as an ATP sensor . Similarly, Raghunathan et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The very C‐terminal helix 2 in the ε e state interacts with the subunits α, β and γ . For some bacterial enzymes it was shown that the CTD of subunit ε has an ATP‐binding motive that can act as an ATP sensor . Similarly, Raghunathan et al .…”
Section: Discussionmentioning
confidence: 99%
“…proposed a model for the M. mazei Gö1 A‐ATP synthase, where ATP can bind to the CDT of subunit F. In this model, subunit F Mm facilitates the binding of ATP to the nucleotide‐binding site in subunit B . In contrast, unlike the stimulating role of subunit F the CTD of subunit ε in its extended conformation was shown to be an intrinsic inhibitor for ATP hydrolysis, but not for ATP synthesis, to prevent futile ATP hydrolysis at low ATP concentrations . Despite similar domain components subunits F and ε have very different regulatory functions in their respective ATP synthases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In TF 1 , inhibition is apparent only at low concentrations of Mg-ATP (below 50 lM) [16,32]. By contrast, in EF 1 , inhibition is apparent at any concentration of Mg-ATP [33][34][35].…”
Section: Mechanism Of E-inhibitionmentioning
confidence: 96%
“…This conformational change allows the C-terminus of subunit  to reach the α 3 β 3 hexamer. Recent findings clearly demonstrate that the Loop2/helix2 of the C-terminal domain plays a pivotal role in inhibiting activity through decreased rotation by extending duration of the inhibited state [130]. Residues εS108 in loop2 and εY114 have been identified as being important for inhibition [130].…”
Section: Subunit  Of F 1 F O Atp Synthasesmentioning
confidence: 99%